Eco-activist imagery in literary texts for children (a case study of English postmodern fairy tales and short stories) - Alla Tsapiv; Mariia Andrieieva (Когниция, коммуникация, дискурс)
This research focuses on the eco-activist multimodal imagery in English postmodern fairy tales and short stories for children as a crucial tool in meaning-making. It is claimed that literary texts for children dynamically reflect current global trends in culture, environmental pollution, gender equality, and family issues. While some topics remain taboo for young readers, others are increasingly prevalent, gradually replacing magical worlds with more realistic, thought-provoking imagery. It has been observed that in recent years, the participation of young people and children in the eco-activist movement has been increasing. They advocate for environmental preservation and solving urgent environmental problems. Literary texts for children are essential tools for fostering a responsible attitude toward the environment at a young age. Due to them, child-readers are introduced to crucial eco-centric issues and ways of solving them and taught the consequences of their actions on nature. The analysis of our case study reveals that the protagonists of eco-activist fairy tales are primarily children concerned about environmental issues. Shadow narratives and the point of view of the child-focaliser are realized by the visual means, i.e. visual metaphors, salience of definite objects on the pictures, interplay of colours and shapes. It has been observed that visual imagery expands, clarifies environmental protection issues and appeals to the better understanding of child-readers their role in preserving the planet and keeping it clean and safe for living. Visual components clearly show the child-reader the damage caused to the environment by human activity: polluted air, water bodies and cities, injured animals, and deforestation. Important meanings are embedded in the dominant colours of the illustrations: green and blue predominate in the illustrations of nature, while grey and black accompany the images of the results of anthropogenic activity. The victory of Good (nature) in fairy tales is represented by a shift from grey and black to green. Intertextual links between literary texts for children by the same author can be formed through illustrations. Thus, a single fictional world is created in which the eco-activist activity of a child-antagonist is not an isolated phenomenon.